THE EFFECT OF STOP LINE MARKINGS ON THESAFETY OF AIRCRAFT MOVEMENT ON THE APRON - Zulfikar Al Ihsan, Muhammad; Hariyadi, Slamet; Dwi Nastiti, Paramita (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Sam Ratulangi International Airport Manado is a class 1B airport and the second largest on the island of Sulawesi after Sultan Hasanuddin International Airport Makassar. This airport has scheduled flights of around 20-25 flights per day both domestic and international routes. This led to a lot of aircraft movement. Markings on the apron are very important to ensure the safety of aircraft movement, one of which is the stop line mark as a marker of the stopping position of the aircraft. The purpose of this study is to determine the suitability of stop line markings on the apron to applicable regulations and their effect on the safety of aircraft movement if there is a marking's discrepancy. The research methodused is descriptive qualitative, namely the collection of data and information through observation, interviews, and literature studies to then be processed in more detail to get clearer data results. The results of this study found that there was a discrepancy in the stop line markings on the apron of Sam Ratulangi International Airport Manado on parking stands 7, 8, and 9 and this was quite influential on the safety of aircraft movement if the aircraft parked on the wrong stop line, which caused difficulty in the aviobridge docking process to the plane. To overcome this problem is by briefing the marshaller team for adjustment of the aircraft parking position and for the long term is to evaluate the markings then remove the old markings that are not suitable and repaint the new markings in accordance with current regulations and conditions.